IDENTIFICATION OF MISCONCEPTIONS ON THE MATERIAL OF SOUND WAVES USING THE FOUR TIER DIAGNOSTIC TEST IN TOLITOLI REGENCY - Azahra, Hafidza; Pasaribu, Marungkil; Haeruddin, Haeruddin; Zaky, Muhammad; Supriyadi, Supriyadi; Worku, Hassen (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
This research aims to describe the misconceptions that occur in sound wave material in Class VIII Public Middle School Tolitoli Regency by using a four-tier diagnostic test. This type of research is descriptive qualitative. The subjects in this study were 60 students from class VIII of Public Middle School 2 Tolitoli, junior high school Negeri 5 Tolitoli, and Public Middle School 8 Tolitoli. Determination of respondents using a purposive sampling technique, namely by taking respondents who experienced the highest misconceptions as many as 10 students. The results showed that the misconceptions that occurred in students of Public Middle Schools in Tolitoli Regency with low misconception criteria, namely at 27%, The identification results showed that students of Public Middle Schools in Tolitoli had understood the concept of sound waves well so that the results achieved were based on the misconception criteria, namely low.